Study of the external appearance of the beetle Ocypus mus Brulle in Iraq (Journal of the College of Basic Education, 2022)
The model Ocypus mus Brulle was chosen because it represents the characteristics of the family. And I studied the main parts of the body, which are the head, thorax, abdomen and their appendages, in order to evaluate the structures of the external appearance and the extent to which they are relied upon in the classification of species.